Cina Benteng : Identitas, Kewarganegaraan, dan Politik Rekognisi - Eddy Setiawan (Institut Kewarganegaraan Indonesia, 2024)
This article examines the construction of the Cina Benteng identity in Tangerang in relation to Indonesia’s citizenship dynamics and population policy. Through a historical review—from the enactment of Law No. 3/1946, the citizenship division under the 1949 Round Table Conference, the Indonesia–PRC Dual Citizenship Treaty, to Presidential Decree No. 10/1959—this paper demonstrates how legal recognition of Chinese Indonesians often failed to translate into substantive recognition. Soemitro’s Benteng Program, the SBKRI policy under the New Order, and the practice of administrative marking inherited the colonial Staatsblad logic of racial categorization. Referring to Benhabib’s and Honneth’s theories of recognition and alienation, this paper highlights the urgency of a Single Indonesian Citizenship principle, not merely guaranteed on paper but realized through fair population administration—especially through post-Reformasi citizenship policy, the 2006 Citizenship Law, and the e-KTP system. The Cina Benteng case underlines that ethnic recognition and inclusive population governance must be integrated to realise substantive citizenship in the Indonesian context.